2010
DOI: 10.2310/7750.2010.09027
|View full text |Cite
|
Sign up to set email alerts
|

Are Excipients Really Inert Ingredients? A Review of Adverse Reactions to Excipients in Oral Dermatologic Medications in Canada

Abstract: Although there are documented reactions to excipients in other products in the literature, few reports outline reactions to excipients in oral dermatologic medications. Whether this low frequency is accurate or whether it is due to a lack of reporting remains unknown. If the latter reasoning is correct, dermatologists must be more aware of these possible reactions. This article serves as a reference guide for dermatologists to aid in prescribing medications to individuals with known sensitivities and to assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Recently, it has been reported that pharmaceutical excipients are not inert ingredients [22] and we have recently documented the lack of efficacy after the switch from brand to the generic formulation of allopurinol. [23] Although, we are unable to evaluate the role of each excipient in the development of side-effects, in our patient we cannot rule out their involvement in the development of skin rash [Table 1].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, it has been reported that pharmaceutical excipients are not inert ingredients [22] and we have recently documented the lack of efficacy after the switch from brand to the generic formulation of allopurinol. [23] Although, we are unable to evaluate the role of each excipient in the development of side-effects, in our patient we cannot rule out their involvement in the development of skin rash [Table 1].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, it has been reported that pharmaceutical excipients are not inert ingredients[22] and we have recently documented the lack of efficacy after the switch from brand to the generic formulation of allopurinol. [23]…”
Section: Discussionmentioning
confidence: 99%
“…Fourthly, the safety of excipients is recurrently questioned by authorities from the analysis of notable adverse effects imputable to excipients shifting their status from inactive to mystery ingredients, reducing again the width of the fi eld of choice (Noiles and Vender 2010 ).…”
Section: Resultsmentioning
confidence: 99%